التعددية بين الواقعية الاجتماعية والتيارات الفكرية الفلسفية - Fauzan Hamdani (AL-FIKRA, 2005)
The phenomenon of plurality has been found since early establishment of human society. Islam acknowledged its existence and necessity as a social reality, because Allah never creates human being as a prototype that was precisely same with the other. Islam taught its adherents to hold peaceful life beside other religion adherents. The Muslims, for centuries, treated the non-Muslim as their brothers as well as the creature of God. There no prohibition to associate with the non-Muslims as long as it is no connection with the ritual affairs. It was decided by the Prophet an as contained in the Madina Islamic constitution. Peaceful life of neighborhood with the non-Muslims had been held since the establishment of the Islamic State in Madina. Thus, the plurality is not a new problem. In secular globalization era, the West makes pluralism as a philosophical or political-ideological current. Their assert that all religions are same, so that there is no religion which is righter than the other. This is the view that Islam rejects. A Muslim that truly believes in and prides his religion, is of course very confident in Islam as only pleasant religion of Allah. Nevertheless, this case will not make the relationship between man to man defective. The Muslim wherever can constantly live neighborly peacefully with the non-Muslims. This took place since the establishment  of Islamic State in Madina.